«La lengua de la gente común y no los priores de la gramática arábiga». The Doctrina christiana en lengua arábiga y castellana (1566) by Martín Pérez de Ayala - Soto González, Teresa (’Ilu. Revista de Ciencias de las Religiones, 2019)
Despite the abundant production of catecismos in 16th century Spain, few of them were addressed directly to the new converted population, and fewer still were translated into or written in Arabic. Given the dimension of the Morisco question within Catholicism at the time, this scarcity is striking. Archbishop of Valencia and attending member of the Council of Trent, Martín Pérez de Ayala (1504-1566), commissioned one of these rare texts, the Doctrina Christiana en Lengua Arauiga y Castellana (1566), written in Valencian Arabic. The text encloses a brief catechism containing mainly prayers but also a set of instructions about both Arabic phonetics and doctrinal matters. The present article intends to study the language ideology present in the translation of Christian doctrine into Arabic. In order to do so, it asks questions such as whether the emphasis on spoken Arabic is a conscious distance from a Koranic Arabic language, and how religious space is shaped through language.